Making the sustainability hotspot analysis more participatory—experiences from field research in Zambia - Droppelmann, Klaus; Müller, Carolin (Frontiers in Sustainable Food Systems, 2023)
Food value chains constitute a core element of food systems. Along any value chain, several bottlenecks, and obstacles negatively affect the sustainability of the entire chain. Therefore, the identification and assessment of such sustainability hotspots is a vital step in the process towards higher levels of sustainability. Over the past few decades food value chains have been supported as part of development cooperation to help alleviate poverty and ensure food and nutrition security. However, so far, a suitable methodology to assess aspects of sustainability along such food value chains was not available. Therefore, we have adapted the sustainability hotspot analysis, originally developed by the Wuppertal Institute, and enhanced it with a participatory approach, thereby making it suitable for application in the context of development cooperation. In this paper, we present a step-by-step overview of the entire assessment process by using examples from its application in Zambia’s dairy and groundnut value chains. The developed methodology allows, through participatory means, the identification and assessment of sustainability aspects by stakeholders themselves, with the validation and amplification of assessment results by locally-based value chain experts. We demonstrate that results from this participatory hotspot analysis are aligned with the principles of agroecology promoted by the FAO, and are geared towards supporting transformative food system change processes. Our key findings from the application of the participatory hotspot analysis showed that sustainability hotspots occur in the social, economic, and ecological dimensions of sustainability along both value chains. It also became clear that hotspots are frequently interconnected, requiring a holistic approach based on a solid understanding of strong sustainability when designing solutions. We conclude that our participatory hotspot analysis provides a user-friendly methodology that generates action-oriented recommendations, and provides an ideal starting point in the development process for co-learning and co-creation of knowledge aimed at generating sustainability-enhancing innovations. The application of the participatory hotspot analysis reveals information on aspects that threaten the sustainability of value chains from a stakeholder perspective. Knowledge of these perspectives is essential, especially for development practitioners tasked with designing implementation strategies to improve the sustainability of value chains.